EVALUATION OF INVESTMENT EFFICIENCY IN NAMANGAN REGION - Baikhanov Bakhodirjon Tursunbaevich; Isakova Naima Ikromzhanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In the article, the results of the evaluation of the effectiveness of the use of investments in the enterprises of Namangan region were developed. The policy of attracting investments for the development of the activities of enterprises using the researches of foreign scientists is aimed at actively attracting investments and their rational use by using the available funds, time and opportunities, improving the economy of the region, encouraging its integration into the world economic system. In the Strategy of Actions on the five priority areas of development of the Republic of Uzbekistan in 2017-2021, the task of "improving the investment environment, actively attracting foreign, first of all, direct foreign investments to the sectors and regions of the country's economy" is defined.